Landscape and Heritage: A Survey and Assessment of Rural Structures in the Province of Colchagua, Chile - Luengo-Moreno, O (UNIV BIO-BIO, 2018)
This research proposes the adoption of a heritage point of view regarding the rural landscape of Colchagua Province, Chile, one that enhances the value of creative capital subject to a resource-based economy that has been capable of building warehouses, corrals, rodeo arenas (medialunas) and covered, open-air stands (ramadas). All these constructions come together as pieces of the landscape that make up an anonymous, scattered, precarious material culture present in the activities of rural life. This research aims to enhance their value by identifying and studying the typologies and characteristics of these pieces as structural and constitutive parts of what it means to inhabit this landscape. Construction operations and time scales are determined, which make it possible to ennoble the aura of austerity and indeterminacy of these structures, through construction logics that recognize scarcity as an opportunity and unite constructive, social and cultural aspects as the synthesis of possible heritage value.